Integrated Media Relations Strategies of the Directorate General of Taxes to Enhance Brand Image - Tin Hartini; Suniah Suniah; Reza Anggriyashati Adara; Vimala Govindaraju; Dila Novita (Jurnal Riset Komunikasi (JURKOM), 2026)
This study examines the media relations strategies employed by the Directorate General of Taxes (DGT) to improve its institutional image. Using a qualitative case study design, data were collected through in-depth interviews, observation of media activities, and analysis of official documents to understand communication practices comprehensively. The findings reveal a structured and sequential media relations process comprising: (1) provision of clear and accurate information materials, (2) facilitation of verification mechanisms, (3) relational engagement with journalists, and (4) integration of the PESO media strategy (paid, earned, shared, and owned media). While empirical evidence on public compliance or brand perception is limited, informants perceive that these strategies enhance transparency, credibility, and accessibility of information, thereby supporting the improvement of DGT’s institutional image. The study proposes a conceptual model illustrating how information supply, verification, relational trust, and multi-channel communication interact to strengthen perceived institutional legitimacy and media relationships. These findings highlight the potential of strategic media relations in public institutions to address negative perceptions and reinforce organizational credibility.